Activated Factor IX Complex in Treatment of Surgical Cases of Hemophilia A with Inhibitors - Hanna, Wahid T; Madigan, Robert R; Miles, Marian A; Lange, Robert D (Thrombosis and Haemostasis, 1981)
Three patients with severe hemophilia A with inhibitors to factor VIII were treated with activated factor IX complex. Bleeiling was controlled adequately during surgical procedures involving each of the three. Partial thromboplastin times showed a variable shortening and prothrombin times were significantly shortened to values less than normal. Hemostasis was substantiated by the use of epsilon aminocaproic acid. Neither anamnestic responses nor thrombotic complications were observed. A transient hypertension developed in two patients shortly after infusion with the activated factor IX complex.
Keywords: Autoplex; Surgical cases; Hemophilia A with inhibitors